Anti-plane crack emanating from the interface in a bounded smart PEMO- elastic structure - Rogowski, Bogdan (Zielona Góra: Uniwersytet Zielonogórski)
The magnetoelectroelastic analysis of two bonded dissimilar piezo-electro-magneto-elastic ceramics with a crack perpendicular to and terminating at the interface is made. By using the Fourier integral transform (in perpendicular directions in each materials), the mixed boundary conditions and continuity conditions are transformed to a singular integral equation with generalized Cauchy kernel, the solution of which has been well studied, and classical methods are directly applicable here to obtain the closed form solution. The results are presented for a permeable crack under anti-plane shear loading and in-plane electric and magnetic loadings, as prescribed electric displacement and magnetic inductions or electric and magnetic fields.
Keywords: interface; anti-plane shear crack; singularity of power law; field intensity factors; magnetoelectroelastic behaviour; Fourier transform; Cauchy singular integral equation; exact solution